AN ANALYTICAL STUDY OF THE GROWTH OF NEW MEDIA ART WITHIN INDIAN VISUAL ART PRACTICES - Mishra, Sanjeev Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Artistic creativity has always evolved in response to cultural contexts and the intent of individual artists. In the contemporary digital age—often framed as a postmodern or even post-postmodern reality—visual art practices are undergoing profound transformations. Technological advancements are reshaping the way art is produced, disseminated, and experienced, and neither galleries nor museums are exempt from this shift. By the mid-1990s, a growing number of Indian artists began exploring installation art, site-specific works, and digital mediums, even as others continued to engage with conventional forms such as painting, sculpture, and printmaking.